Analysis of soft skills in teachers and their impact on professional performance - Farías Moreira, Carmen; Reina Guaña, Erika (mktDESCUBRE; Vol 1 No 24 (2024): Twenty-fourth Edition (July - December)DO - 10.36779/mktdescubre.v1i24.877, 2024)
The present article, based on a non-experimental quantitative approach, analyzes the relationship between soft skills and the professional performance of teachers at the Instituto Superior Tecnológico Luis Tello. The objective was to identify areas for improvement and propose training strategies to strengthen these competencies. The methodology included a cross-sectional and descriptive-correlational design, applying structured surveys to 12 teachers, complemented by a bibliographic analysis. The results showed that 69.2% of the teachers possess notable soft skills, such as responsibility, adaptability, and information management, while communication and interpersonal development competencies presented a medium positive correlation. Additionally, 92.3% of participants demonstrated communicative empathy, although with room for improvement in its consistent application. The conclusions emphasize the need to implement continuous training programs to optimize these skills, which are essential for educational quality and holistic development. This study serves as an initial basis for future research with broader scope, involving a larger sample to deepen the analysis of these competencies in educational contexts.